Soluble Fas Ligand Is Essential for Blister Formation in Pemphigus - Lotti, Roberta; Shu, En; Petrachi, Tiziana; Marconi, Alessandra; Palazzo, Elisabetta; Quadri, Marika; Lin, Ann; O’Reilly, Lorraine A.; Pincelli, Carlo (Frontiers in Immunology, 2018)
Pemphigus is a blistering disease characterized by autoantibodies (PVIgG) directed mostly against desmogleins (Dsgs), resulting in loss of keratinocyte adhesion (acantholysis). Yet, the mechanisms underlying blister formation remain to be clarified. We have shown previously that anti-FasL antibody (Ab) prevents PVIgG-induced caspase-8 activation and Dsg cleavage in human keratinocytes, and that sera from pemphigus patients contain abnormally increased levels of FasL. Here, we demonstrate that recombinant FasL induces activation of caspases prior to Dsg degradation, and anti-FasL Ab prevents acantholysis in cultured keratinocytes. Moreover, silencing of FasL reduces PVIgG-induced caspase-8 activation and Dsg3 cleavage. Following injection of PVIgG into mice, FasL is up-regulated at 1-3 hrs and is followed by caspase-8-mediated keratinocyte apoptosis, before blister formation. Administration of anti-FasL antibody after PVIgG injection blocks blister formation in mice. Furthermore, we injected PVIgG into two different gene-targeted mutant mice that selectively lack either secreted soluble FasL (sFasL), FasLΔs/Δs mice, or the membrane-bound form of FasL (mFasL), FasLΔm/Δm mice. After PVIgG treatment, blisters are only visible in FasLΔm/Δm animals, lacking mFasL, but still producing sFasL, similar to WT (C57BL/6) animals. In contrast, a significant decrease in the relative acantholytic area is observed in the FasLΔs/Δs animals. These results demonstrate that soluble FasL plays a crucial role in the mechanisms of blister formation, and blockade of FasL could be an effective therapeutic approach for pemphigus.